Pendugaan Mutu Genetik Induk Ikan Patin Siam (Pangasius hypophthalmus) dari Beberapa Sentra Produksi Benih Berdasarkan Keragaan Anakannya - Didik Ariyanto; Bambang Gunadi; Sularto Sularto (Universitas Gadjah Mada, 2007)
The purpose of this research was to estimate the genetic quality of siamese catfish (Pangasius hypophthalmus) from various seed production centres.The broodstocks genetic quality were estimated based on their progeny performances.The result showed that the population growth rates, individually average weight, FCR, survival rate and productivity of seeds from Central Java (Ungaran), West Java (Sukamandi and Sukabumi) and Jakarta were 6.89, 6.08, 5.61 and 5.37 g/day; 47.08, 39.64, 36.80 and 35.51 g/individually fish; 0.82, 0.87, 0.94 and 1.00; 76.80, 86.77, 86.43 and 85.66%; 366.99, 343.95, 318.02 and 304.21 kg/10.000 fishes/8 weeks, respectively.